A contingency-configurational view of purchasing operations: The mediating role between supplier relationship and firm performance. Issue 1 (January 2023) - Franco, Cíntia Wilke; Benitez, Guilherme Brittes; de Sousa, Paulo Renato; Kliemann Neto, Francisco José; Frank, Alejandro G.
Abstract: The literature has considered purchasing and supply management activities from a strategic perspective, but the tactical role of purchasing operations has yet to be explored. Purchasing operations represent the internal modus operandi for transactions with suppliers, comprising three main activities – purchasing transactions, purchasing document management, and purchasing assessment – and supportive activities like purchasing knowledge management. Following the contingency theory, we hypothesize that these internal activities mediate between external supplier relationship management and firm performance (financial, customer and delivery performance). Complementarily, we adopt the configurational theory to hypothesize that this link between external and internal activities can be combined to increase firm performance. To test this contingency-configurational view of purchasing operations, we conducted a quantitative survey with 234 companies. The regression results of the contingency analysis show that purchasing operations activities have a full mediation role in most relationships between supplier relationship management and firm performance, while knowledge management positively moderates the association between purchasing assessment and customer performance. Moreover, the cluster analysis for the configurational analysis shows that supplier relationship management and purchasing operations follow maturity levels of joint implementation of internal and external activities. Our findings shed light on the purchasing operations by defining the activities representing this concept and showing their role in supply management. We also contribute to practice by proposing an integrative system that helps managers organize the firm's purchasing and supply management activities. Highlights: Purchasing operations as a mediator between supplier relationship and performance. Purchasing knowledge management as moderator of Purchasing Operations on performance. Cluster analysis to define patterns of purchasing operations and supply management. Three performance metrics assessed: financial, customer satisfaction, and delivery. Data analysis from a survey of 234 companies.